PENERAPAN EVIDENCE BASED NURSING DENGAN INTERVENSI INOVASI ELEVASI KAKI 30º DAN ANKLE PUMPING EXERCISE TERHADAP EDEMA KAKI PADA PASIEN GAGAL GINJAL KRONIK DIRUANG INTENSIVE CARE UNIT (ICU) A2 RS. BHAYANGKARA TK. I R. SAID SUKANTO - Tsania Ramadhanty (2022)
Chronic kidney failure is a disease that attacks the kidneys and causes a decrease or weakening of the performance of the kidney organs, decreased kidney function can cause fluid accumulation, accumulation of body metabolic waste, and electrolyte imbalances in the body resulting in accumulation of fluid in the body which ends with leg edema. The implementation of this activity is to analyze the effectiveness of the intervention of 30 feet elevation and Ankle Pumping Exercise on leg edema in patients with chronic kidney failure in the Intensive Care Unit. After the innovation intervention for 3 consecutive days showed a decrease in foot edema by measuring pitting edema, namely the depth of pitting edema on the right leg was 4 mm, and the left leg was 3.5 mm. While the measurement of foot circumference showed a decrease of 3.2 cm on the right leg and 3 cm on the left foot. Based on the analysis of the innovation intervention, it can be concluded that the administration of 30º leg elevation therapy and Ankle Pumping Exercise to patients with chronic kidney failure in the Intensive Care Unit (ICU) has proven effective in reducing leg edema by measuring leg circumference and pitting edema